Inovasi Pengelolaan Zakat di Era Digital (Studi Akses Digital Dalam Pengumpulan Zakat) - Holilur Rahman (Dirosat : Journal of Islamic Studies, 2021)
The potential for zakat collection in Indonesia is always growing, but it is unproportional to the results of the collection. The objective conditions of COVID-19 which force people to indirect interaction have an effect on changes in the lifestyle of the digitalist society. This is used as the basis for the amil zakat institution to continue to improvise zakat collection. The strategy carried out by amil zakat institutions, especially the National Amil Zakat Agency, is by utilizing digital platforms with various innovations in collaboration with fundraising partners. The purpose of this study was to determine the innovations of the amil zakat institution on optimizing zakat collection in the digital era. This research method uses a type of qualitative research that is descriptive analytical. The results show that innovations of digital zakat collection by facilitating muzakki in paying zakat can increase zakat collection optimally.Â Potensi pengumpulan zakat di Indonesia senantiasa berkembang, namun tidak berbanding lurus dengan hasil pengumpulannya. Kondisi objektif covid-19 yang memaksa masyarakat tidak berinteraksi langsung berefek terhadap perubahan gaya hidup masyarakat yang digitalis. Hal tersebut dijadikan landasan bagi institusi amil zakat untuk terus melakukan inovasi pengumpulan zakat. Strategi yang dilakukan institusi amil zakat khususnya Badan Amil Zakat Nasional dengan memanfaatkan platform digital dengan berbagai inovasi yang berkolaborasi dengan mitra fundraising. Tujuan penelitian ini untuk mengetahui inovasi institusi amil zakat dalam mengoptimalkan pengumpulan zakat di era digital. Metode penelitian ini menggunakan jenis penelitian kualitatif yang bersifat deskriptif analitis. Adapun hasilnya menunjukkan bahwa inovasi pengumpulan zakat digital dengan mempermudah muzakki dalam menunaikan zakat dapat meningkatkan pengumpulan zakat secara optimal.